The Social Accountability towards Employees and its Effect on the Labours’ Ethics at Wad Medani Teaching Hospital, Gezira State, Sudan) - Ali, Malik Elnaeim MohD.; El Sharief, Najwan Hashim El Noor; E.B, Haydar (Gezira Journal of Health Sciences; Vol 14 No 1 (2018), 2018)
هدف الدراسة هدفت الدراسة لبحث المسؤولية الإجتماعية تجاه العاملين (أطباء والفنيين والإداريين) وإنعكاسها على اخلاقيات العمل فى مستشفى ودمدني التعليمي  بولاية الجزيرة وعلاقة ذلك بالبعد الأخلاقي ودراسة الإختلاف في أبعاد المسؤولية الإجتماعية وأبعادأخلاقيات العمل.  وإلى معرفة إهتمام ادارة مستشفى ودمدني التعليمي بالمسؤولية الإجتماعية. طريقة البحث  تم جمع البيانات عن طريق الإستبيان والملاحظة من خلال أختيار عينة عشوائية من الأطباء والفنيين والإداريين البالغ عددهم 120 فردا، أتبعت الدراسة المنهج الوصفي التحليلي لتحليل البيانات بإستخدام برنامج الحزم الإحصائية للعلوم الإجتماعية (SPSS) نتائج الدراسة خلصت الدراسة الى أن مستشفى ود مدني التعليمي يوفر خدمات التأمين الصحي  فقط للمبحوثين ولا تولي أهتمام بالخدمات الأخرى من العلاج بالخارج وتدريب الموظفين وخدمات إعانات الزواج وتقديم منح دراسية للأطباء للفنيين والإداريين. وكذلك عدم توفر بيئة عمل مناسبة فى مستشفى ودمدني التعليمي للأطباء والفنيين والاداريين مما أدى إلى إنخفاض أداء العاملين، وأيضا عدم التبليغ عن الممارسات السلبية الأخلاقية في المستشفى. ويعتمد المستشفى نظام الحوافز عند الأداء المميز، وتوجد فوارق في مستوى البعد الاخلاقي تبعاً لمتغير الوظيفة. تعزى المفارقات في المسؤولية الإجتماعية للفوارق الوظيفية فى مستشفى ود مدني التعليمي للأطباء والفنيين والاداريين. التوصيات أوصت الدراسة إلى إهتمام مستشفى ود مدني التعليمي بخدمات إعانات الزواج وتقديم المنح الدراسية والعلاج بالخارج عند الحاجة وتدريب الموظفيين، والعمل على خلق بئية عمل مناسبة. Objective and Background: The aims of the study are to pay attention to the social accountability towards doctors, managers and technicians who work in Wad Medani Teaching Hospital (WTH) – Gezira State Sudan, study the relation between the social accountability and the ethical dimensions, and to study the differences in the social responsibility and the ethical dimensions of the study groups. Method: This is an analytical descriptive study. The data was collected via a questionnaire and observations, by choosing a random sample of 120 individuals of various study groups. The data was analyzed by using the statistical computer programme (SPSS). Results: WTH provides health insurance services but other services such as medical treatment abroad, cadres training or training its, funding matrimonial services, good working environment, the influence or improve staff performance were not catered for. The study showed imprecision in reporting about the passiveness and bad behavior of staff. The hospital depends on giving incentives system for the distinguished performance, there is also a diversity in the ethical dimension level according to the job’s specifications and diversities in the social accountability attributed to the jobs’ diversities. Recommendations: The Hospital has to consider offering scholarships for training. It has to provide chances for medical treatment outside Sudan, and to look after training its cadres, paying attention to the hospital’s environment, to develop a method of staff performance reporting.